Strategi Peningkatan Kapasitas Pelaksanaan Manajemen Terpadu Balita Sakit melalui in House Training - Yudiernawati, Atti; Abiddin, Andi Hayyun (Universitas Malahayati, 2024)
ABSTRACT The beginning of a child's life is the most appropriate time to provide encouragement or development efforts so that children can develop optimally. However, awareness and concern for health from an early age still leaves many problems. The presence of health problems will interfere with growth and development. Management is needed in providing care to sick children. To identify the effectiveness of the model on the ability of health workers in implementing IMCI. Research design uses quantitative with a quasi-experimental one group pretest – posttest approach carried out at the Malang City Community Health Center. The population of this study is health workers consisting of nurses and midwives who work at the KIA Polyclinic Community Health Centers in the Malang City area, a total of 15 Community Health Centers. The sample will be taken using a purposive sampling technique totaling 64 people who meet the inclusion criteria: 1) Nurses and midwives with at least D-III graduates, 2) have worked for at least 2 years, 3) Not on leave. Data analysis was carried out using unpaired t test. Before (pre) participating in training via In house training (experiential learning), there were 52 people who had a sufficient level of knowledge in MTBS Implementation, and 12 other people already had a good level of knowledge. Meanwhile, after (post) participating in training via In house training (experiential learning), there were 35 people who had a sufficient level of knowledge in IMCI Implementation, and 29 other people already had a good level of knowledge with a p value of 0.001. The experiential learning model with the In House Training (IHT) approach is effective for increasing the knowledge of health workers in implementing IMCI Keywords: In House Training, Experiential Learning, Knowledge, MTBS ABSTRAK Awal kehidupan anak merupakan masa yang paling tepat dalam memberikan dorongan ataupun upaya pengembangan agar anak dapat berkembang secara optimal. Namun, kesadaran dan kepedulian terhadap kesehatan sejak dini masih menyisakan banyak persoalan. Adanya masalah kesehatan akan mengganggu tumbuh kembangnya. Diperlukan suatu manajemen dalam memberikan perawatan pada anak sakit. Mengidentifikasi efektifitas model terhadap kemampuan tenaga kesehatan dalam implementasi MTBS. Desain Penelitian menggunakan kuantitatif dengan pendekatan quasy eksperimental one group pretest – posttest yang dilakukan di Puskesmas wilayah kota Malang. Populasi penelitian ini merupakan tenaga kesehatan terdiri dari perawat dan bidan yang bertugas di Poli KIA Puskesmas wilayah Kota Malang sejumlah 15 Puskesmas. Sampel akan diambil dengan teknik purposive sampling berjumlah 64 orang yang sesuai dengan kriteria inklusi: 1) Perawat dan bidan minimal lulusan D-III, 2) telah bekerja minimal 2 tahun, 3) Tidak dalam kondisi cuti. Analisis data dilakukan dengan menggunakan unpaired t test. Pada saat sebelum (pre) mengikuti pelatihan melalui In house training (experiential learning), ada sebanyak 52 orang yang mempunyai tingkat pengetahuan yang cukup dalam Implementasi MTBS, dan 12 orang lainnya sudah mempunyai tingkat pengetahuan yang baik. Adapun saat sesudah (post) mengikuti pelatihan melalui In house training (experiential learning), ada sebanyak 35 orang yang mempunyai tingkat pengetahuan yang cukup dalam Implementasi MTBS, dan 29 orang lainnya sudah mempunyai tingkat pengetahuan yang baik dengan p value 0.001. Model pembelajaran experiential learning dengan pendekatan In House Training (IHT) efektif untuk meningkatkan pengetahuan tenaga kesehatan dalam menerapkan MTBS Kata Kunci: Pelatihan Internal, Pembelajaran Berdasarkan Pengalaman, Pengetahuan, MTBS